STRATEGI PERCEPATAN PENGEMBANGAN INDUSTRI TURUNAN MINYAK SAWIT MENTAH (MSM) DI INDONESIA - Didik Mochamad Rofiqi, M Syamsul Maarif, dan Aji Hermawan (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
To increase competitiveness of Indonesia to be the world oleochemical leader as targeted in theNational Industrial Development Master Plan (RIPIN) 2035, Indonesia must have thirty-three time capacity ofthe current oleochemical industry.To meet the objective, a strategy to accelerate the development of downstreampalm oil industry is needed. The successful development industries are required consider competitive advantage(Diamond Porter) and the alternative strategic of development. Alternative strategics were collected fromexperts with interactive method. Determining acceleration strategy was conducted by analytical hierarchyprocess (AHP). The results of identification based Diamond Porter showed that the current research anddevelopmentdid not support the downstream palm oil industries, in adequate infrastructure, an oligopoly marketstructure, and inconsistence of the government's commitment. Alternatif strategic of the development ofdownstream industries consistsed of simplification of licensing, preparation of infrastructure, tax incentives,financial support, the government's commitment, and market certainty. Results of the AHP showed thatgovernment's commitment was priority-base alternative with highest priority value of 0.31 compared to otheralternatives.Keywords: AHP, alternative strategic, diamond porter, interactive method, palm oil